Edgar Wind i oblicza sztuki nowoczesnej. Na marginesie książki Bena Thomasa - Kasperowicz, Ryszard (Artium Quaestiones, 2022)
The issue of the relationship between art history, its analytical procedures and critical judgements, and the attitude of art historians to modern art has long been a problem discussed when we refer, for example, to scholars such as Riegl, Wölfflin, and, for obvious reasons, Justi or Sedlmayr. Although many art historians reacted very negatively to their own contemporary artistic phenomena, of which Justi’s aversion to Impressionism was perhaps the most notable example, the issue is by no means clear-cut. It is important to note here that even critical remarks made against distinct phenomena in modern art need not be tantamount to a condemnation of “modernity”. Edgar Wind, an outstanding methodologist of science and an excellent art historian of the 18th century and the Renaissance, seems to be a particularly interesting example here. Criticising various manifestations of the cult of “pure form”, and associating them with the influence of Romantic “autonomy” of art creation and certain concepts from the sphere of art history as a discipline, Wind was at the same time a very insightful observer of contemporary art, valuing selected artists highly. This issue was presented in detail by Ben Thomas in his recently published book on Wind’s attitude to contemporary art, drawing on Wind’s previously unpublished and unknown materials. The present text is an attempt at a broader, problematising discussion of this issue on the basis of reading Ben Thomas’s book, the publication of which should be regarded as an important event in the field of research into the history of art, history of art history, and the influence exerted by art history as a practice and as a discipline on the problem of esteeming modern art.